The subject and non-subject agreements in the Yemsa relative clauses - Mitike Asrat (Peoples' Friendship University of Russia (RUDN University), 2024)
This study aims to elucidate the subject and non-subject agreement mechanisms within Yemsa relative clauses, an area not comprehensively covered by existing research. By analysing these agreement forms, the study seeks to bridge the identified gap in the understanding of Yemsa's syntactic structures. The research questions guiding this study focus on the mechanisms through which subject agreements are manifested in Yemsa's relative clauses and the morphological markers they employ, alongside an examination of how non-subject agreements within these clauses diverge from subject agreements. The data were collected through the elicitation technique through informant interviews about subject and non-subject agreements in the Yemsa relative clauses. The data were analysed using a descriptive approach. The person-marker inventories are suffixes. Siewierska's Prominence Hierarchy works in Yemsa. The order of the suffixes is modifier > head. Person markers simultaneously indicate masculine and feminine referents and numbers. Siewierska's Predicate Hierarchy works on Yemsa. The suffix element -nà appears in the relative verbs. The word order in the relative clause is (O)VS. The nominative case is unmarked, whereas the accusative case is marked. The subject argument is expressed in the same manner as an independent clause. The description of the subject and the non-subject agreement in the Yemsa relative clauses has significant implications for developing the general features of Omotic and Afroasiatic languages. The study will serve as an input for the preparation of pedagogical materials in the language.